2013
DOI: 10.1109/twc.2013.090513.122056
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Near Capacity of Non-Binary LDPC Coded Large MIMO Systems with a Novel Ultra Low-Complexity Soft-Output Detector

Abstract: Recently, it has been proved that both MMSE and MF detectors are near optimal detection for large scale MIMO systems, e.g., MIMO systems with hundreds of antennas. In order to attain near capacity region with reasonable complexity, lowcomplexity detector with soft-output generation is necessary for coded large MIMO systems. We show in this paper that the nonbinary LDPC codes and well-known soft-output MMSE detector can be utilized to significantly reduce the gap to capacity. We also propose a novel soft-output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Additionally, they applied various detectors, including the MMSE detector, the PDA detector, the LAS detector and the RTS detector, in high-rate non-orthogonal STBC aided LS-MIMO systems [128], [328], [329]. Furthermore, it was shown that non-binary LDPC coded LS-MIMO systems are capable of achieving a near-capacity performance with MMSE detection [336]. It should be noted that in principle a variety of other metaheuristics based MUDs, such as the genetic algorithm (GA) based MUD [529]- [535], the ant colony optimization (ACO) based MUD [537]- [541], the particle swarm optimization (PSO) aided MUD [545]- [547], and the simulated annealing (SA) assisted MUD [548], [549], may also be extended to the LS-MIMO context.…”
Section: Recent Advances In Ls-mimo Detectionmentioning
confidence: 99%
“…Additionally, they applied various detectors, including the MMSE detector, the PDA detector, the LAS detector and the RTS detector, in high-rate non-orthogonal STBC aided LS-MIMO systems [128], [328], [329]. Furthermore, it was shown that non-binary LDPC coded LS-MIMO systems are capable of achieving a near-capacity performance with MMSE detection [336]. It should be noted that in principle a variety of other metaheuristics based MUDs, such as the genetic algorithm (GA) based MUD [529]- [535], the ant colony optimization (ACO) based MUD [537]- [541], the particle swarm optimization (PSO) aided MUD [545]- [547], and the simulated annealing (SA) assisted MUD [548], [549], may also be extended to the LS-MIMO context.…”
Section: Recent Advances In Ls-mimo Detectionmentioning
confidence: 99%
“…Following are some examples. Modified MMSE and matched filter (MF) soft-output detection [45] and the FG-based BP detection with Gaussian approximation of interference (FG-GAI BP) [37], [46], [47] were considered in designing LDPC codes for massive MIMO systems. Iterative soft-input soft-output (SISO) MMSE detectors were proposed to enhance the signal detection of massive MIMO systems [17]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since decoding process requires additional computational complexity, a low-complexity detection algorithm had better be applied to JDD. In [30], non-binary LDPC codes are designed for coded massive MIMO systems considering modified MMSE and matched filter (MF) soft-output detectors. In [31]- [33], binary and non-binary LDPC codes for massive MIMO systems using the FG-GAI BP detection are designed.…”
Section: Introductionmentioning
confidence: 99%